2013
DOI: 10.1007/s10551-013-1661-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Perspectives in Work Disability Prevention and Return to Work: Toward a Common Vocabulary for Analyzing Stakeholders’ Actions and Interactions

Abstract: Many studies have emphasized the importance of medical, insurance and workplace systems treating individuals fairly in work disability prevention (WDP) and return-to-work (RTW). However, ethical theories and perspectives from these different systems are rarely discussed in relation to each other, even though in practice these systems constantly interact. This paper explores ethical theories and perspectives that may apply to the WDP-RTW field, and discusses these in relation to perspectives attributed to domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…Ennek egyik folyományaként mérési pontként és mérőszámként is megjelenik a fogyatékossággal élő személyek foglalkoztatása, de miközben tudatosan figyelik a költségeket, mégsem csupán a "business case" logika vezeti magát a foglalkoztatást, hanem erősen megjelennek az etikai érvek is (Reed, 2003;Stahl et al, 2013). Mindkét szervezetre jellemző a CSR, a felelősség komplex értelmezése: nem kom-munikációs, PR-célokat követnek, hanem társadalmi (különösen a belső érintettekre, a munkavállalókra vonatkozó) szemléletformálás és változtatás a kimondott cél.…”
Section: Következtetésekunclassified
“…Ennek egyik folyományaként mérési pontként és mérőszámként is megjelenik a fogyatékossággal élő személyek foglalkoztatása, de miközben tudatosan figyelik a költségeket, mégsem csupán a "business case" logika vezeti magát a foglalkoztatást, hanem erősen megjelennek az etikai érvek is (Reed, 2003;Stahl et al, 2013). Mindkét szervezetre jellemző a CSR, a felelősség komplex értelmezése: nem kom-munikációs, PR-célokat követnek, hanem társadalmi (különösen a belső érintettekre, a munkavállalókra vonatkozó) szemléletformálás és változtatás a kimondott cél.…”
Section: Következtetésekunclassified
“…In 2014, Ståhl et al [26] noted that ethics involves models about what are ''good'' actions and also the criteria related to identifying them. Helmchen, in 2015 [27], noted that contemporary psychiatric ethics deals with reflection on the manner in which moral norms of a general nature are applied to psychiatric situations that are specific.…”
Section: Psychiatric Ethicsmentioning
confidence: 99%
“…So once I got home some of the letters and things became less clear as time went on; I also didn't have the support services to explain what they were actually asking. (Male, [30][31][32][33][34][35][36][37][38][39] Several claimants suggested that it would have been useful to have the services of a non-legal advocate or consultant to manage their claim, arrange transport to appointments and explain entitlements in the early stages:…”
Section: (B) Non-legal Supportmentioning
confidence: 99%
“…To me it was pretty obvious that I had something go wrong, I wasn't a fake. (Male, [30][31][32][33][34][35][36][37][38][39] Some claimants perceived the CO's suspicion of wrongdoing as an attack on their personal integrity, that served only to compound stigma they already felt was associated with having a claim:…”
Section: (C) Doubting Motivationmentioning
confidence: 99%
See 1 more Smart Citation